Assessment the Severity of Asthma on Patients in Specialist Respiratory Center in Baghdad City - Sabah A. Ahmed; Ali kh. Aliwie (Kufa Journal for Nursing Sciences)
Objectives: The study aims to assess the patients' asthma control and find out the association between the gender, age, marital status, educational level, employment, duration of disease.